A survey of aflatoxin M1 contamination in raw milk produced in urban and peri-urban areas of Kisumu County, Kenya. Issue 1 (1st January 2018) - Anyango, Gladys; Mutua, Florence; Kagera, Irene; Andang`O, Pauline; Grace, Delia; Lindahl, Johanna F.
ABSTRACT: Background: Food safety is of increasing global concern, and a OneHealth issue requiring attention of many disciplines. Aflatoxins are toxins produced by fungi and found in foods and feeds, and exposure causes negative health effects in humans and animals. When lactating animals consume aflatoxin B1, the metabolite (AFM1) is transferred to milk. Methods: A cross-sectional study was designed to determine characteristics of smallholder dairy farming in urban and peri-urban areas of Kisumu and quantify AFM1 in milk. Data was collected from 97 randomly selected dairy farms on farming practices, milk production, and awareness about aflatoxins. Collected milk samples were analyzed using enzyme-linked immunosorbent assay for AFM1. Results: Average milk produced was 13 liters per day per household and mainly used for household consumption and sold to neighbours. Farmers mainly fed cows on forage and concentrates (62.9%). Levels of AFM1 ranged from below the detection limit to 151 ppt, with a mean of 29.67 ppt; 26.4% exceeding the EU limit. Concentrate feeding was associated with higher AFM1 levels (p = 0.002); with farms feeding concentrates more likely to have levels exceeding 50 ppt (OR = 10.1). Conclusion: In conclusion, milk produced by small holder dairy farmers in Kisumu County frequently is contaminated with AFM1, implying health risks for human and animals.